Pengaruh Kepuasan Kerja Terhadap Kinerja Dokter yang Dimoderasi oleh Spiritualitas - Pandu Prashanantyo; Iwan Setiawan Adji; Rini Kuswati; Kussudyarsana Kussudyarsana (Jurnal Manajemen Kesehatan Indonesia, 2023)
Job satisfaction is a positive emotional condition as a result of job appraisal. Spirituality possessed by a doctor is an inner condition that grows because it interprets work in his life. This study aims to examine and explain the relationship between job satisfaction and physician performance, which is moderated by spirituality. From the questionnaires that were distributed, a total of 150 respondents were obtained consisting of general practitioners (71 people), doctors with Masters degrees (65 people), specialist doctors (9 people) and doctors with Doctoral education as many as 5 people. The doctors have worked for < 5 years (63 people), 5-10 years (32 people), 10-20 years (31 people) and > 20 years (24 people). The results of the construct validity test (job satisfaction) obtained data that there were 5 valid statement indicators. While the validity of spirituality obtained 4 valid data, and on the performance, parameters obtained 6 valid performance indicators. The results of the analysis obtained data that job satisfaction has a positive significant effect on the performance of doctors (P = 0.000). Spirituality has a positive significant effect on doctors' performance with a significance level of P=0.000. However, spirituality as a moderating variable has a negative effect, which means it reduces the effect of job satisfaction on performance. The spirituality factor reduces job satisfaction. It can be logically explained that job satisfaction is not solely a determinant of performance. Spirituality reflects the vocation of dedication as a doctor who has special knowledge to help human health and humanity. Spiritually, working doctors do not pursue job satisfaction merely, but there is a spirituality of dedication that aims to help save the souls of fellow human beings.